2019
DOI: 10.1212/wnl.0000000000008357
|View full text |Cite
|
Sign up to set email alerts
|

The natalizumab wearing-off effect

Abstract: Objective Natalizumab is effective in treating relapsing-remitting multiple sclerosis (RRMS). However, many patients report an increase of multiple sclerosis symptoms at the end of the natalizumab cycle: a wearing-off effect. The objective of this study was to evaluate the prevalence of the wearing-off effect in patients with standard and extended intervals and to study possible associations with pharmacokinetic/dynamic measurements and patient characteristics in a prospective, monocenter, cross-sectional coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In the previously mentioned Norwegian study, the wearing-off effect was associated with lower α4 integrin receptor occupancy. However, van Kempen et al 12 found that the wearing-off effect was more frequently reported by patients receiving natalizumab every four weeks than in those treated with extended interval dosing. With respect to B-cell depletion, patients whose rituximab treatment is interrupted or stopped still show prolonged disease suppression, even when alternative DMT is not started.…”
Section: Discussionmentioning
confidence: 99%
“…In the previously mentioned Norwegian study, the wearing-off effect was associated with lower α4 integrin receptor occupancy. However, van Kempen et al 12 found that the wearing-off effect was more frequently reported by patients receiving natalizumab every four weeks than in those treated with extended interval dosing. With respect to B-cell depletion, patients whose rituximab treatment is interrupted or stopped still show prolonged disease suppression, even when alternative DMT is not started.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may also experience infusion reactions (although more likely to occur during initial infusion) [7] or develop an intolerance to preinfusion medications use. Finally, patients may request a return to NTZ having seen a decline in a sense of "the feel-good effect" described with the drug [8], which has previously been described as a main reason for switching back to NTZ [9].…”
Section: Discussionmentioning
confidence: 99%